Combined use of right ventricular coupling and pulmonary arterial elastance as a comprehensive stratification approach for right ventricular function - Yihang Wu; Pengchao Tian; Lin Liang; Yuyi Chen; Jiayu Feng; Boping Huang; Liyan Huang; Xuemei Zhao; Jing Wang; Jingyuan Guan; Xinqing Li; Yuhui Zhang; et al. (Wiley, 2023)
Abstract Right ventricular (RV)‐pulmonary arterial uncoupling is the consequence of increased afterload and/or decreased RV contractility. However, the combination of arterial elastance (Ea) and end‐systolic elastance (Ees)/Ea ratio to assess RV function is unclear. We hypothesized that the combination of both could comprehensively assess RV function and refine risk stratification. The median Ees/Ea ratio (0.80) and Ea (0.59 mmHg/mL) were used to classify 124 patients with advanced heart failure into four groups. RV systolic pressure differential was defined as end‐systolic pressure (ESP) minus beginning‐systolic pressure (BSP). Patients among different subsets showed dissimilar New York Heart Association functional class (V = 0.303, p = 0.010), distinct tricuspid annular plane systolic excursion/ pulmonary artery systolic pressure (mm/mmHg; 0.65 vs. 0.44 vs. 0.32 vs. 0.26, p < 0.001), and diverse prevalence of pulmonary hypertension (33.3% vs. 35% vs. 90% vs. 97.6%, p < 0.001). By multivariate analysis, Ees/Ea ratio (hazard ratio [HR] 0.225, p = 0.004) and Ea (HR 2.194, p = 0.003) were independently associated with event‐free survival. Patients with Ees/Ea ratio greater than or equal to 0.80 and Ea less than 0.59 mmHg/mL had better outcomes (p < 0.05). In patients with Ees/Ea ratio greater than or equal to 0.80, those with Ea greater than or equal to 0.59 mmHg/mL had a higher adverse outcome risk (p < 0.05). Ees/Ea ratio less than or equal to 0.80 was associated with adverse outcomes, even when Ea was less than 0.59 mmHg/mL (p < 0.05). Approximately 86% of patients with ESP‐BSP greater than 5 mmHg had an Ees/Ea ratio less than or equal to 0.80 and/or an Ea greater than or equal to 0.59 mmHg/mL (V = 0.336, p = 0.001). Combined use of Ees/Ea ratio and Ea could be a comprehensive approach to assessing RV function and predicting outcomes. An exploratory analysis demonstrated that Ees/Ea ratio and Ea might be roughly estimated based on RV systolic pressure differential.